Optimizing Maritime Supply Chains: Enhancing Network Efficiency, Process Innovation, and Sustainable Logistics Management in Sea Transportation - Suhartini Suhartini; Marudut Bernadtua Simanjuntak (Global Research Collaboration, 2026)
Maritime supply chains are increasingly under pressure to improve operational efficiency, reduce environmental impact, and adapt to fluctuating global trade conditions. However, existing frameworks for optimization often fall short in integrating network-level analysis with sustainability goals and process improvement initiatives. This study explores the optimization of maritime supply chains through a comprehensive analysis of network structure, operational efficiency, process innovation, and sustainable logistics practices. Using a qualitative research approach that includes thematic analysis, cross-group comparisons, and narrative synthesis, the research draws on insights from maritime logistics operators, supply chain strategists, sustainability experts, and academics. Key findings highlight four main themes: the multi-layered structure of maritime supply chain networks and the factors influencing their efficiency, the role of process innovation and digital transformation in enhancing logistics operations, the challenges of incorporating sustainability into supply chain optimization, and the governance mechanisms needed to balance efficiency with resilience and environmental responsibility. This study presents an integrated framework for optimizing maritime supply chains, linking network efficiency, process innovation, and sustainability governance, providing valuable theoretical insights and actionable recommendations for maritime stakeholders navigating the complexities of modern global sea transportation logistics.